Síndrome de Sweet associada a linfoma de Hodgkin: relato de caso Sweet's Syndrome associated with Hodgkin's disease: case report - Carolina Villela da Rocha Miranda; Fernanda de Marca Filgueiras; Daniel Lago Obadia; Alexandre Carlos Gripp; Maria de Fátima Scotelaro Guimarães Alves (Sociedade Brasileira de Dermatologia, 2011)
A síndrome de Sweet é enfermidade cutânea rara e de etiologia pouco esclarecida. Cerca de 20% dos casos são associados a neoplasias hematológicas, sendo raros os casos relacionados à doença de Hodgkin. Relata-se caso de paciente masculino de 57 anos que desenvolveu a síndrome concomitantemente à neoplasia. As doenças foram controladas com o tratamento específico. Sweet's syndrome is a rare cutaneous disease of unknown etiology. About 20% of the cases are associated with hematological neoplasms, and cases related with Hodgkin's disease are rare. We present the case of a 57-year old male patient who developed the syndrome concomitantly with the neoplasm. The diseases were controlled with specific treatment.